Physical and morphometric characteristics of unidentified cattle breed of Northern Karnataka region of India - Mundinamani, Vijaylaxmi I; Gouri, Mahadevappa D; Prasad, Kotresh; Patil, Vivek M (Indian Journal of Dairy Science, 2024)
Indigenous cattle are capable of converting low-quality feeds and fodder more efficiently into animal products, and are better adapted to withstand tropical diseases. Therefore, the conservation of indigenous animal resources has been proposed as a viable strategy for reducing the extinction of livestock breed diversity. A study was undertaken to characterise the non-descript cattle of North Karnataka region. Raichur and Yadgir districts were randomly selected and divided into two blocks each and five villages were selected in each block. The morphological characteristics of male and female cattle of 0-3 months, 3-6 months, 6-12 months, 1 to 3 years and >3 years age was recorded from totally 388 animals. The results indicated that these cattle were short in nature, docile in temperament with three colour variants viz., brown, black and white. These cattle are called Javari in their breeding tract. Horn of these cattle was directed upward, medium sized with horizontal ears. The average horn length, chest girth, body length and height at withers (cm) were 19.63±0.49, 142.81±0.88, 118.73±0.81 and 105.89±0.48 in adult cows respectively, whereas in adult bulls were 26.65±0.61, 173.23±1.20, 142.15±1.08 and 118.05±0.56, respectively. These cattle were reared under semi intensive system, sent for grazing in the day time without any supplemental feeding and kept under kutcha housing or in open space during night hours. Therefore it was evident from the current experiment, that these cattle were having unique characteristic feautres, hence there is a need for their identification for conservation as indigenous genetic resource.